Calculus II Course Redesign: Supporting Faculty in Pedagogical Change. Issue 3 (28th May 2021) - Carney, Debra; Sanders, Megan; Spiegel, Samuel; Swanson, Rebecca; Vasquez, Ariana
ABSTRACT: This article describes a partially flipped course design for Calculus II which has been implemented by a varied instructional team at a medium-sized public engineering university (Colorado School of Mines (Mines)) over a period of three years. We have identified three main factors which have contributed to the success of the implementation: (1) institutional support for teaching, (2) use of evidence-based practices, and (3) creation of faculty community. We demonstrate both student and faculty success through student assessment data and faculty interviews. Success is defined in terms of student performance, the implementation rate of faculty, and the positive experience of the instructional team.